Long-distance sensor network based on ZigBee for monitoring and risk management in Quindío-Colombia area (Revista de Investigaciones Universidad del Quindío, 2014)
The department of Quindio is a high-population area in Colombia, which is threatened by earthquakes and landslides. These landslides are a result of water accumulation due to heavy rains and triggered by seismic effects. Although geological and hydrological studies show high risk of landslides in this area, and despite the existence of government policies for risk management, there are no real-time networks for monitoring and firing early-warning alarms. In this paper, we present the design of a low-cost wireless sensor network for monitoring hydro-climatological variables based on ZigBee technology. We emphasize on the design considerations of the sensor nodes, communication policies and strategies adopted to allow communication for distances up to 8 km. Our design is validated by field measurements, which show the feasibility of using ZigBee communication over long distances.
Keywords: Risk management; Wireless Sensor Networks; ZigBee; Hydro-climatogical variables; Early-Warning Systems